Merangkai Potensi Budaya dan Alam Pusparahayu melalui Eksplorasi Lodong Gejlig, Kukuk, dan Cilongan - Risma Julistiana; Selvi Andini; Rian Maulana Hidayat; Arji Arafah Sodik; Sovia Lestari; Julfikar Aria Wibisana; Muhammad Dani (Journal of Empowerment Community, 2026)
This community service activity was conducted in Pusparahayu Village, Puspahiang Sub-district, Tasikmalaya Regency, which possesses rich cultural heritage, traditional art, distinctive handicrafts, and promising ecotourism potential. The main objective of this activity was to explore and document three local assets: the traditional art of Lodong Gejlig, the Kukuk handicraft, and the Cilongan ecotourism area, as part of efforts to preserve and promote local potential to a wider audience. The methods applied included field observation, interviews with artists, craftsmen, and ecotourism managers, as well as visual documentation of cultural and natural activities. This activity adopted a participatory approach, involving students and local communities in the processes of exploration, data collection, and dissemination of results. The findings revealed that Lodong Gejlig reflects the community’s values of togetherness and creativity, Kukuk demonstrates both aesthetic and economic potential, while Cilongan holds great promise as an eco-based educational and recreational destination. Through the documentation and publication of these explorations, this community service activity is expected to raise public awareness of the importance of preserving local culture and nature while promoting sustainable village development.